(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The topic of protests and Islam’s stance on them are covered in this study. In recent years, there has been a discernible rise in demonstrations in many nations, with people taking to the streets and other locations for a variety of causes, such as political, social, economic, and so forth. These events, which are ways of expressing opinions, might be referred to as protests or demonstrations. Plan of research: It included three chapters, a preface, an index, a conclusion, and an introduction. There are the following chapters: - The definition of demonstrations and terms associated with them are covered in the first chapter. It has two prerequisites: The first prerequisite is a linguistic and terminological definition of demonstrations. The second prerequisite consists of terms associated with protests and their distinctions, such as rebellion, banditry, and strike. - The second subject is the sorts and purposes of protests in Islam: It has two prerequisites: The first prerequisite is the purpose of Islamic protests. The types and sorts of demonstrations are the second prerequisite. - The third topic is Islamic laws governing protests and their management. It has two prerequisites: The first prerequisite is Islamic regulations on demonstrations and protests. The second prerequisite is the Islamic ruling concerning protests. The most significant findings I came to after conducting the research are included in the conclusion. These findings include: - The term "demonstrations" is not new and normally refers to advocacy and support, but in modern times, it has come to refer to gatherings that take place in the streets and on public roads for the sake of an interest or to combat corruption. - Demonstrations are mostly used to communicate and express opinions, whether they be ones of satisfaction or dissatisfaction, and their motivations are centered around seeking an interest or combating corruption.